Molecular Docking of 3,7-Dihydroxy-2-phenyl-4H-chromen-4-one as a LOX Inhibitory Compound - Rehman, Taj Ur; Zeb, Muhammad Aurang; Liaqat, Wajiha; Xiao, Wei-Lie (PSM Biological Research, 2018)
The present study was carried out to explore phytochemically and pharmacologically the medicinal plant botanically classified as Millettia ovalifolia. The structure of the isolated compound 3,7-Dihydroxy-2-phenyl-4H-chromen-4-one was confirmed by modern spectroscopic techniques besides its comparison with analytical data available in literature. The compound was further studied for lipoxygenase (LOX) inhibitory activity and docking studies. The compound was found to reveal important LOX inhibitory potential with the IC50 value 31.92±0.02 ?M. The molecular docking study further showed the important molecular interactions between the compound and LOX displaying encouraging activity for more optimization as an approaching anti-inflammatory lead compound. The results showed that this plant is very significant and can act as a source to treat inflammation.